1978
DOI: 10.1111/j.1476-5381.1978.tb07808.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tryptophan Metabolism on the 5‐hydroxytryptamine and Kynurenine Pathways in a Strain of Rats With a Deficiency in Platelet 5‐ht

Abstract: Brain 5‐hydroxytryptamine (5‐HT) metabolism has been compared in albino (Sprague‐Dawley; SD) and in Fawn‐Hooded (FH) rats, which have an inherited platelet 5‐HT deficiency. It was confirmed that blood 5‐HT levels in the FH rats were about one quarter of those in the SD rats. Brain 5‐HT and 5‐HIAA were however higher in FH rats on a per gram basis; there was no difference between the strains on a per brain basis, because of the smaller brain weights of the FH rats. Brain and plasma tryptophan were not significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…In contrast to body weight, the FH/HamSlc rats exhibited a lower brain weight than the F344 rats (Table 1). This is concordant with a previous study that reported a reduced brain volume in FH rats compared to Sprague-Dawley rats (Joseph, 1978). Neural loss or brain atrophy is also often observed in patients with depression and bipolar disorder (Bora et al, 2010; Selvaraj et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast to body weight, the FH/HamSlc rats exhibited a lower brain weight than the F344 rats (Table 1). This is concordant with a previous study that reported a reduced brain volume in FH rats compared to Sprague-Dawley rats (Joseph, 1978). Neural loss or brain atrophy is also often observed in patients with depression and bipolar disorder (Bora et al, 2010; Selvaraj et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…FH rats have a spontaneous mutation of the recessive red-eyed dilution gene (also known as Rab38 ) on chromosome 1 (Prieur and Meyers, 1984) and exhibit dysfunctional 5-HT release from platelets, as well as serotoninergic system alterations in the central nervous system (Gudelsky et al, 1985; Joseph, 1978; Tschopp and Zucker, 1972). Consistent with previous studies (Joseph, 1978), we found a reduction in plasma 5-HT levels in the FH/HamSlc rats compared with the F344 rats (Table 2). Furthermore, the concentration of tryptophan was low in the plasma but high in the brain, particularly in the prefrontal cortex (Table 2, Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After 1 or 2 h the rats were decapitated and blood and brains collected. Plasma tryptophan, brain tryptophan, 5-HT & 5-HIAA were determined fluorimetrically as previously described (Joseph, 1978) as was corticosterone (Mattingly, 1962). The experiments showed that the rise in brain tryptophan induced by restraint stress in rats (60.2% at 1 h and 39.7% at 2 h P < 0.001) was prevented by administration of valine 200 mg/kg i.p.…”
Section: Saline 30mentioning
confidence: 99%